Genetic inheritance of multiple traits of blast, bacteria leaf blight resistant and drought tolerant rice lines - Mohd Rafii Yusop (International Journal of Applied Biology, 2019)
Rice (Oryza sativa L.) is a cereal and staple food crop of over half of the world’s population. Blast, bacteria leaf blight and drought stresses affect yield of rice drastically ranging from 1-100% loss depending on the severity of disease and water deficit condition. Resistance and tolerance high yielding varieties of blast (Putra1) and drought (MR219 IR99784-156-137-1-3) respectively and also IRBB60 (bacteria leaf blight) were used. The research considered the genetic inheritance of the new improved lines and their interactions. Pedigree breeding method was used to develop two single, double and three-way (and reciprocal) crosses through marker-assisted selection. Southern blot analysis was used to determine success of introgression of resistance/tolerance genes/QTLs and selection, also validated by phenotyped results. Agro-morphological and yield parameters of the various populations were analysed. The results indicated levels of significant differences amongst and between treatments for non-drought stress (NS) and reproductive drought stress (RS) and their interactions. There were significant variation among parents and improved lines on some traits in NS treatment, but RS significantly affected parameters of DF, FFG, YM and most especially the susceptible parent, while the improved lines were tolerant.  Significant interactions was recorded (P≤0.05) between treatment and variety (Trt*Var.) on PL, T, FFG and GLW. Cluster analysis and PCA of relationship among the 9 traits in the two treatments revealed that each of single, double and three-way (and reciprocal) crosses had good lines either under NS and RS.